Production of fibrinogenolytic and fibrinolytic enzymes by a strain of Penicillium sp. isolated from contaminated soil with industrial effluent - Lillian Maria Baggio; Luciano Aparecido Panagio; Fabiana Guillen Moreira Gasparin; Daniele Sartori; Maria Antonia Pedrine Colabone Celligoi; Cristiani Baldo (Universidade Estadual de Maringá, 2019)
Cardiovascular diseases associated with thrombosis are one of the main causes of death all around the world. Urokinase, streptokinase, and tissue plasminogen activator are the major thrombolytic agents used to treat thrombosis. However, the fact that these agents have several side effects and high prices has driven the search for safer and more economically viable compounds for the treatment of cardiovascular diseases. Thus, the aim of this study was to evaluate the potential of fungi isolated from industrial effluents to produce fibrino(geno)lytic enzymes. The selection of the protease-producing strains showed that only the BF20 strain was able to produce proteolytic halos in milk agar. This strain identified as belonging to the genus Penicillium was cultivated in submerged fermentation. Different media composition were tested to evaluate proteolytic activity, and the results showed that the medium containing 0.1% yeast extract and 1% skim milk, pH 5.0, present higher azocaseinolytic activity (0.24 U mL-1 min.-1). This sample also showed the ability to degrade fibrinogen and fibrin after 15 and 120 min. of incubation, respectively. These results indicate that the BF20 strain has a thrombolytic potential, effectively degrading fibrinogen and fibrin, having great application in the health area.